Cutaneous manifestations in patients with inflammatory bowel disease - Barquero-Orias, Daniel (2026)
The extra-intestinal manifestations of inflammatory bowel disease are common, these can be encountered before the diagnosis of the gastrointestinal entity and can follow the course of their activity. Moreover, the use of new drugs including biological and immunosuppressive therapies adds additional associations in these patients. There is an association with pyoderma gangrenosum, erythema nodosum, Sweet syndrome, aphthous ulcers, hidradenitis suppurativa, vasculitis, lupus erythematosus-like syndrome, infections, skin malignancy, psoriasiform dermatitis and eczematous reactions. It is important for the professional to have knowledge about these because of the additional mortality and morbidity in patients with Crohn disease and ulcerative colitis. The objective of this article is to provide relevant information regarding the epidemiology, pathogenesis, diagnosis, therapeutics, and prognosis of the most frequent entities associated with inflammatory bowel disease.